Kepemimpinan Kharismatik Gus Dur dalam Perspektif Pendidikan Pancasila: Internalisasi Nilai Kemanusiaan, Toleransi, dan Demokrasi - Antonius Bere; Clotilde Seran (Jurnal Media Administrasi, 2025)
This paper aims to explore the charismatic leadership model of Abdurrahman Wahid (Gus Dur) from the perspective of Pancasila Education, with an emphasis on the internalization of human values, tolerance, and democracy embedded in the national and cultural praxis. Using a approach based on literature study, this article shows how Gus Dur became a transformative leader who consistently realized the second, third, and fourth principles of Pancasila. His leadership not only defended the nation's plurality but also created interreligious dialogue spaces and protected minority groups as concrete manifestations of humanity and tolerance values. Furthermore, the deliberative democracy he pioneered remains a significant legacy for political education and national character development.